Kajian Sosio-Yuridis Pembebasan Bersyarat dan Pemberian Asimilasi Bagi Narapidana pada Masa Pandemi Covid-19 Ditinjau Dari Perspektif Tujuan Pemidanaan - Fernando Tantaru; Elsa Rina Maya Toule; Erwin Ubwarin (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2021)
Introductioan: One of the programs in the correctional guidance system is the provision of assimilation, which is part of the development program of the correctional institution. In connection with the current Covid-19 outbreak, the government has made a policy for the release of prisoners, the government has established it through the assimilation program and the right to integration. The presence of integration assimilation aims to support the eradication of Covid-19 in correctional institutions (LAPAS) and detention centers (RUTAN).Purposes of the Research: Assessing and analyzing from a socio-juridical perspective, conditional and assimilation for prisoners during the Covid-19 pandemic in terms of the perspective of the purpose of punishment and after the prisoner is in the community. Methods of the Research: The research method used is empirical legal research, with the form of evaluative research which aims to assess the implementation of laws and regulations and is carried out by conducting library research and field research. The type of research used in this writing is analytical descriptive. Which is a method that serves to describe or provide an overview of the object under study through data that has been collected through interviews and observations. Results of the Research: From the results of the research conducted by the writer at the Ambon Class IIA Prison (LAPAS) and the Ambon Class II Correctional Center (BAPAS) regarding Assimilated Prisoners. and the process of resocialization and reintegration of prisoners with society and its socio-juridical impact. and the supervision process which is still relatively weak due to its access, such as the lack of Android as a media for guidance and supervision of the sharing community of prisoners who carry out assimilation at home, and also the distance of prisoners' houses which is quite difficult to reach. to be contacted in the middle of the Covid-19 Pandemic administratively (Rapid-Test Letter) for Community Advisors.